Small-Signal and Noise Model Determination for Double Polysilicon Self-Aligned Bipolar Transistors - A. Caddemi; M. Sannino (Active and Passive Electronic Components)
In this paper, noise characterization and modeling of a double polysilicon self-aligned bipolar transistor are presented. The device has been characterized in terms of noise and scattering parameters by means of an original automatic noise figure measuring system only. Measurements have been performed over the 1–4 GHz frequency range and at different bias conditions. The extracted model refers to the performance of the chip device since the package and bond parasitics have been accurately de-embedded by proper calibration techniques.